Organogenesis in eggplant (Solanum melongena L. cv. Embu) as affected by antibiotics and growth regulators - Picoli, E. A. de T.; Cecon, P. R.; Fári, M. G.; Otoni, W. C. (International Journal of Horticultural Science, 2002)
The influence of antibiotics (cefotaxime, timentin, kanamycin and hygromycin) and growth regulators (indolacetic acid and 6-benzylaminopurine) was evaluated on eggplant organogenesis. Solanum melongena hypocotyl segments (6 to 10 mm length), taken from 16 to 20-days in vitro grown seedlings, were used as explants. The basic medium was composed by MS salts, Gamborg vitamins and 2% sucrose, solidified with agar 0.8% and pH adjusted to 5.7±0.2. Morphogenesis was impaired at 50 to 100 mg L-I kanamycin and 7.5 mg L-1 hygromycin. Both Timentin and cefotaxime reduced the frequency of regenerating explants meanwhile hyperhydricity was not affected. A decrease in root regeneration was observed with increasing cefotaxime concentrations, although, timentin had no effect on root regeneration, as compared to the control treatment. Interestingly, the number of adventitious roots was more noticeable at 0.25 mg L-I IAA plus 0.5 mg L-1 BAP. However, if just IAA was added led to higher number of regenerated roots compared to other treatments.